An experimental medicine decipher of a minimum correlate of cellular immunity: Study protocol for a double-blind randomized controlled trial - Shirin Kalimuddin; Shirin Kalimuddin; Yvonne F. Z. Chan; October M. Sessions; October M. Sessions; October M. Sessions; Kuan Rong Chan; Eugenia Z. Ong; Eugenia Z. Ong; Jenny G. Low; Jenny G. Low; Jenny G. Low; et al. (Frontiers in Immunology, 2023)
Vaccination induces an adaptive immune response that protects against infectious diseases. A defined magnitude of adaptive immune response that correlates with protection from the disease of interest, or correlates of protection (CoP), is useful for guiding vaccine development. Despite mounting evidence for the protective role of cellular immunity against viral diseases, studies on CoP have almost exclusively focused on humoral immune responses. Moreover, although studies have measured cellular immunity following vaccination, no study has defined if a “threshold” of T cells, both in frequency and functionality, is needed to reduce infection burden. We will thus conduct a double-blind, randomized clinical trial in 56 healthy adult volunteers, using the licensed live-attenuated yellow fever (YF17D) and chimeric Japanese encephalitis-YF17D (JE-YF17D) vaccines. These vaccines share the entire non-structural and capsid proteome where the majority of the T cell epitopes reside. The neutralizing antibody epitopes, in contrast, are found on the structural proteins which are not shared between the two vaccines and are thus distinct from one another. Study participants will receive JE-YF17D vaccination followed by YF17D challenge, or YF17D vaccination followed by JE-YF17D challenge. A separate cohort of 14 healthy adults will receive the inactivated Japanese Encephalitis virus (JEV) vaccine followed by YF17D challenge that controls for the effect of cross-reactive flaviviral antibodies. We hypothesize that a strong T cell response induced by YF17D vaccination will reduce JE-YF17D RNAemia upon challenge, as compared to JE-YF17D vaccination followed by YF17D challenge. The expected gradient of YF17D-specific T cell abundance and functionality would also allow us to gain insight into a T cell threshold for controlling acute viral infections. The knowledge gleaned from this study could guide the assessment of cellular immunity and vaccine development.Clinical trial registrationClinicaltrials.gov, NCT05568953.